Inovasi dan Tantangan Pengarusutamaan Gender di Kementerian Lingkungan Hidup dan Kehutanan Republik Indonesia - Ernawati Eko Hartono; Khulfi Muhammad Khalwani (Jurnal Perempuan, 2022)
The issue of gender equality in various fields related to natural resource management, including the environment and forestry, has long been a concern of social researchers, especially the issue of gender bias in the planning, management, marketing and access to benefits and/or impact recipients. This paper aims to provide a descriptive analysis of the innovations and challenges of implementing Gender Mainstreaming (PUG) carried out by Government Agencies, namely the Ministry of Environment and Forestry (KLHK). Gender Mainstreaming is a strategy to achieve gender justice and equality through policies, programs and activities that take into account the experiences, aspirations, needs and problems of men and women in the process of monitoring and evaluating all aspects of life and development. The method used is a desk study and interviews. The results of the analysis show that the PUG policy in the KLHK has been able to encourage internal parties in the KLHK to pay more attention to the issue of gender equality, both from the leadership aspect and in the implementation of programs/activities. These innovations must continue to be developed consistently, so that they can also be a driving force and an example for other government agencies, both at the central and regional levels.